STRATEGI PENGELOLAAN KAWASAN SUAKA MARGASATWA BALAI RAJA BERDASARKAN PERUBAHAN TUTUPAN LAHAN - Ade Riccard Simatupang; Aslim Rasyad; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2020)
Forests are an invaluable source of natural wealth and have a strategic value, because forests greatly affect humans and wildlife. Area Balai Raja wildlife reserve Bengkalis Regency, Riau Province was established by the government with the aim of protecting Sumatran Elephants (Gajah Sumatera). The existence of the region experiences pressure from the community through activities, from the local government and oil and gas companies. The research objective is to formulate a management strategy based on changes in land cover. The study was conducted for 3 (three) months at Balai Raja wildlife reserve. The research approach used is a qualitative approach with survey methods and management strategy analysis using SWOT analysis. The results showed that the change in land cover in Balai Raja wildlife reserve Area was due to the presence of oil and gas company activities, community activities and local government activities. The largest change in land cover occurred in 1990 to 2000, where the largest reduction occurred in the secondary swamp forest 8,982.26 hectares, whereas from 2000 to 2010, the largest change in land cover occurred in the swamps of 509.55 hectares and in 2010 to 2015 the largest change in land cover occurred in plantations of 68.2 hectares. Management strategies based on land cover, namely 1) increasing the synergy and cooperation in the management of the area which includes, area boundaries, preservation of flora and fauna as well as awareness and improvement of community welfare, 2) increasing the involvement of related parties in the management of Balai Raja wildlife reserve, 3) restore function area, 4) community involvement in the management of Balai Raja SM Area, 5) Encourage research and development activities on the potentials contained within the Balai Raja SM Area